Effect of epoxy macromolecules as interfacial mediators on the microstructure and physical properties of styrene butadiene rubber/talcum powder composites - Qilai Wang; Guangyang He; Gang Gao; Xianrong Shen; Yixin Xiang (Resources Chemicals and Materials)
Poly(isoprene-co-glycidyl methacrylate) epoxy macromolecules were synthesized via reversible addition-fragmentation chain transfer (RAFT) polymerization to act as interfacial mediators between talcum powder (Talc) and styrene-butadiene rubber (SBR) with the aim of improving the properties of SBR/Talc composites. The epoxy macromolecules were uniformly dispersed on the surface of Talc using the spray-drying method. Subsequently, the modified Talc was utilized in the preparation of SBR composites. During hot vulcanization, isoprene double bonds could directly graft onto the rubber skeleton. Simultaneously, the epoxy groups opened the ring and formed covalent bonds with silanol. The interfacial covalent bonds were found to significantly enhance the dispersion of Talc and the interfacial interactions between SBR and Talc, as evidenced by scanning electron microscopy, cross-linking density measurements, and rubber processing analyzer tests. Differential scanning calorimetry results indicated that the number of interfacial covalent bonds and the content of glassy layers in the composites increased with the rise in GMA content and modified Talc. At equivalent filler loadings, epoxy macromolecules with 20 wt% and 34 wt% GMA increased the tensile strength by 31 % and 49 %, respectively. Concerning viscoelastic properties, composites containing interfacial covalent bonds exhibited superior stress relaxation and stress softening properties.